Alteration of Gut Microbiota: New Strategy for Treating Autism Spectrum Disorder - Liu, Jiayin; Gao, Zhanyuan; Liu, Chuanqi; Liu, Tianyao; Gao, Junwei; Cai, Yun; Fan, Xiaotang (Frontiers in Cell and Developmental Biology, 2022)
Autism spectrum disorder (ASD) is defined as a complex heterogeneous disorder and characterized by stereotyped behavior and deficits in communication and social interactions. The emerging microbial knowledge has pointed to a potential link between gut microbiota dysbiosis and ASD. Evidences from animal and human studies showed that shifts in composition and activity of the gut microbiota may causally contribute to the etiopathogenesis of core symptoms in the ASD individuals with gastrointestinal tract disturbances and acts on microbiota-gut-brain. In this review, we summarized the characterized gut bacteria composition of ASD, and the involvement of gut microbiota and their metabolites in the onset and progression of ASD, the possible underlying mechanism are also highlighted. Given this correlation, we also provide an overview that the mainly microbial-based therapeutic interventions such as probiotics, antibiotics, microbiota transfer therapy, and dietary interventions. And address their potential benefits on behavioral symptoms of ASD. The precise contribution of altering gut microbiome to treating core symptoms in the ASD need to be further clarified, it seemed to open up promising avenues to develop microbial-based therapies in ASD.